2011
DOI: 10.1038/ng.790
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale analysis of the regulatory architecture of the mouse genome with a transposon-associated sensor

Abstract: We present here a Sleeping Beauty-based transposition system that offers a simple and efficient way to investigate the regulatory architecture of mammalian chromosomes in vivo. With this system, we generated several hundred mice and embryos, each with a regulatory sensor inserted at a random genomic position. This large sampling of the genome revealed the widespread presence of long-range regulatory activities along chromosomes, forming overlapping blocks with distinct tissue-specific expression potentials. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
163
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(170 citation statements)
references
References 50 publications
7
163
0
Order By: Relevance
“…This plasmid was linearized and randomly integrated into the genome of polymorphic Mus musculus/Mus castaneus embryonic stem cells carrying an ms2-tagged Xist ( [Jonkers et al 2008], a gift from Joost Gribnau) using standard procedures. Integration sites of 56 colonies were identified by nested PCR using transgene-specific primers and a partially random primer as described (Ruf et al 2011), followed by Sanger sequencing. LacO tethering experiments were performed on clone 36 (integration site Chr 11: 115,708,347).…”
Section: Generation Of Laco Transgenic Cellsmentioning
confidence: 99%
“…This plasmid was linearized and randomly integrated into the genome of polymorphic Mus musculus/Mus castaneus embryonic stem cells carrying an ms2-tagged Xist ( [Jonkers et al 2008], a gift from Joost Gribnau) using standard procedures. Integration sites of 56 colonies were identified by nested PCR using transgene-specific primers and a partially random primer as described (Ruf et al 2011), followed by Sanger sequencing. LacO tethering experiments were performed on clone 36 (integration site Chr 11: 115,708,347).…”
Section: Generation Of Laco Transgenic Cellsmentioning
confidence: 99%
“…By profiling the contacts of a given gene promoter, 4C-seq technology allows the identification of the genomic territory within a TAD containing all the CREs that regulate that promoter, what is defined as the regulatory landscape (RL) of that particular gene [12]. Indeed, functional studies in mouse embryos using a transposon-associated sensor [13] have shown that these contact profiles correspond to large regulatory domains typically found around developmental genes [14-16·]. This improved knowledge of the genomic organization in animals, much more realistic and biologically informed, poses new questions to our current understanding of transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…27; and pig,. Genome-wide mutational screens using gene-trap versions of these vectors have also been carried out successfully in several vertebrate species (20,(31)(32)(33)(34).The aim of this study was to evaluate whether DNA transposons can be used to increase the efficiency of the genetic The authors declare no conflict of interest. …”
mentioning
confidence: 99%
“…13 [28][29][30]. Genome-wide mutational screens using gene-trap versions of these vectors have also been carried out successfully in several vertebrate species (20,(31)(32)(33)(34).…”
mentioning
confidence: 99%